Studi Uji Kesesuaian Selisih Lapangan Kolimasi pada Pesawat Mammografi Analog dan Digital - Fitriani Fitriani; Bualkar Abdullah; Dahlang Tahir (Jurnal Fisika FLUX, 2019)
Study of collimation field difference suitability test on analog and digital mammography at leading hospital in Makassar from 2016-2018. This test was carried out by using four coins of the same size placed on the edge of the collimator lamp field, one different size coin was placed on the table edge of the chest wall section, and one coin was placed on the surface under the compression pedal to coincide with the edge of the chest wall. The results of the p value obtained for each measurement point, both for the difference of the light collimation field toward the X-ray beam and the difference of X-ray beam collimation field toward image receptor have the same value of 0.000 (p < 0.05). This value states that there are significant differences in the collimation field difference from 2016-2018. The results of collimation field difference suitability test on analog and digital mammography are still within the tolerance limits recommended by BAPETEN, for the difference of the light collimation field toward X-ray beam ≤ 1% SID and the difference of X-ray beam collimation field toward image receptor ≤ 2% SID. This shows that mammography is feasible and able to operate safely for patients and non-patients.